Analysis of Banks' Health Before and After Consolidated - Jayanthi Shekarmodo Jawotho; Wahyudi Wahyudi (Budapest International Research and Critics University, 2022)
The purpose of this study was to determine the difference in the soundness of the Bank before and after consolidation using the Risk-Based Bank Rating (RBBR) method. In this study, the Bank's soundness level consists of four variables, namely risk profile, good corporate governance (GCG), earnings (profitability), and capital (capital). This study uses banking companies that are consolidating with the aim of meeting the minimum core capital of banks according to the Financial Services Authority Regulation concerning the Consolidation of Commercial Banks of 20 banks, with the final sample of the study as many as 15 banks. The data used is secondary data with a sample collection method using purposive sampling. The data analysis technique in this study used the Wilcoxon signed rank test, with the help of the SPSS 25.0 application.